2016
DOI: 10.1016/j.envpol.2016.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bisphenol A (BPA) on early embryo development in the marine mussel Mytilus galloprovincialis: Effects on gene transcription

Abstract: Bisphenol A (BPA), a monomer used in plastic manufacturing, is weakly estrogenic and a potential endocrine disruptor in mammals. Although it degrades quickly, it is pseudo-persistent in the environment because of continual inputs, with reported concentrations in aquatic environments between 0.0005 and 12 μg/L. BPA represents a potential concern for aquatic ecosystems, as shown by its reproductive and developmental effects in aquatic vertebrates. In invertebrates, endocrine-related effects of BPA were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 47 publications
(55 reference statements)
5
81
1
1
Order By: Relevance
“…The results show that in mussel hemocytes V. tapetis induced a time dependent decrease in the immunoreactive band corresponding to p-mTor. Transcripts for mTor have been identified in the tissues Mytilus edulis [30]; moreover, we have recently shown that the level of mRNA for mTor are significantly modulated during early embryo development in M. galloprovincialis [31]. However, in the present work, Western blot with antibodies to total, unphosphorylated mTor showed a high variability of the signal in control hemocytes (not shown); therefore, the level of p-mTor was evaluated by densitometric analysis of the mTor/actin ratio.…”
Section: Discussionmentioning
confidence: 98%
“…The results show that in mussel hemocytes V. tapetis induced a time dependent decrease in the immunoreactive band corresponding to p-mTor. Transcripts for mTor have been identified in the tissues Mytilus edulis [30]; moreover, we have recently shown that the level of mRNA for mTor are significantly modulated during early embryo development in M. galloprovincialis [31]. However, in the present work, Western blot with antibodies to total, unphosphorylated mTor showed a high variability of the signal in control hemocytes (not shown); therefore, the level of p-mTor was evaluated by densitometric analysis of the mTor/actin ratio.…”
Section: Discussionmentioning
confidence: 98%
“…EPp, the most abundant serum protein in M. galloprovincialis, is an acidic, histidine-rich, cation binding glycoprotein; it has a complex and anomalous N-glycan structure and contains a conserved C1q complement domain. Due to its peculiar composition, EPp is involved in multiple functions, from shell formation to immune response (42)(43)(44). This protein has been shown to play a key role in specific recognition of both selected bacterial strains and NP types.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed no effect of the plastic treatments in the capacity to fight viral infections in D. melanogaster . Previous studies had reported effects in the immune system of several models by increase of immune cell numbers, physiological changes or protein or gene overexpression ( Canesi et al, 2015 ; Balbi et al, 2016 ; Greven et al, 2016 ; Sadler, Brunner & Plaistow, 2019 ; Hirt & Body-Malapel, 2020 ). Other studies found injection of latex beads (composed of polystyrene) used to block phagocytosis ( Elrod-Erickson, Mishra & Schneider, 2000 ) can increase susceptibility to some pathogens ( Costa et al, 2009 ; Lamiable et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%